The role of satellite TV channels in creating a cultural and social value conflict for Algerian rural children:a field study of a sample of rural families in Tiaret - Kheira Benmeftah (Social Empowerment Journal, 2021)
This study seeks to ascertain the degree of value conflict (social and cultural) resulting from the Algerian child's use of satellite television channels - from the parents' point of view - where the measure of value conflict was questioned and applied to a sample of its size: 160 families residing in different rural areas of Tiaret State, the study concluded:The child's daily viewing of satellite television channels occurs during the evening. As a result of watching satellite television channels, the level of educational attainment of children has declined, as has the cultural patterns that these channels broadcast. The degree of value conflict in children is increasing with the increase in the duration of their use of space. Differences in the degree of conflict are attributable to the variability of family type, the educational level of parents. There are no differences in the degree of conflict attributable to the sex (gender) variable and the standard of living of the researched families.